The Involvement of Cell Adhesion Molecules, Tight Junctions, and Gap Junctions in Human Placentation - Adu-Gyamfi, Enoch Appiah; Czika, Armin; Gorleku, Philip Narteh; Ullah, Amin; Panhwar, Zulqarnain; Ruan, Ling-Ling; Ding, Yu-Bin; Wang, Ying-Xiong (Reproductive sciences (Thousand Oaks, Calif.), 2021)
Placentation is a major determinant of the success of pregnancy. It is regulated by several factors such as cell adhesion molecules, tight junctions, and gap junctions. The cell adhesion molecules are integrins, cadherins, immunoglobulins, nectins, and selectins. The tight junctions are composed of claudins, occludin, and junction adhesion molecule proteins while the gap junctions are composed of connexins of varying molecular weights. During placentation, some of these molecules regulate trophoblast proliferation, trophoblast fusion, trophoblast migration, trophoblast invasion, trophoblast-endothelium adhesion, glandular remodeling, and spiral artery remodeling. There is a dysregulated placental expression of some of these molecules during obstetric complications. We have, hereby, indicated the expression patterns of the subunits of each of these molecules in the various trophoblast subtypes and in the decidua, and have highlighted their involvement in physiological and pathological placentation. The available evidence points to the relevance of these molecules as distinguishing markers of the various trophoblast lineages and as potential therapeutic targets in the management of malplacentation-mediated diseases.